Characterization of the key aroma compounds in cigar filler tobacco leaves from different production regions - Jiang, Chenxi; Lv, Jinxiong; Ji, Lingbo; An, Hongyue; Yang, Mingxuan; Huang, Yang; Liu, Lulu; Jiang, Zhongrong; Xu, Xiujuan; Hu, Jun (Frontiers in Plant Science, 2024)
Cigar tobacco leaves exhibited distinct regional characteristics, and aroma compounds were the key substances determining the different style features of cigars. However, the differences in aroma characteristics and the mechanisms of key aroma compound synthesis have not been fully elucidated. This study collected filler tobacco leaves (FTLs) from 5 representative domestic and international production regions. Gas chromatography-mass spectrometry (GC-MS) identified aroma compounds, an aroma wheel was established based on odor activity values (OAV), and principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) revealed major differences. Synthesis pathways of key differential components were further explored using the Kyoto Encyclopedia of Genes and Genomes (KEGG). In this study, 56 aroma compounds were identified in FTLs. Imported-FTLs (IMP-FTLs) contained higher levels of ketones and esters, along with moderate nicotine content, and exhibited a more noticeable sour and woody aroma. In contrast, Domestic-FTLs (DOM-FTLs) had a greater distribution of aldehydes, phenols, and neophytadiene, presenting a more prominent bean, burnt-sweet, and floral aroma. Nine compounds, including sclareol, 5-methylfurfural, and (E)-5-isopropyl-8-methylnona-6,8-dien-2-one, were identified as key differential components, and their synthesis primarily involves pathways such as phenylalanine metabolism and carotenoid biosynthesis. These findings provided a novel perspective on the targeted enhancement of key aroma compounds, which was significant for improving the aroma quality of filler tobacco leaves.